Pulmonary parenchymal involvement caused by Tropheryma whipplei - Zhang Wen Mei (De Gruyter, 2021)
We report a 26-year-old man with left chest pain for 4 days. His chest CT showed a cavity in the left upper lung. Tuberculosis was suspected first, but metagenomics next generation sequencing (mNGS) in bronchoalveolar lavage fluid only detected Tropheryma whipplei. Tropheryma whipplei is the pathogen of Whipple’s disease. The most frequently involved organs are the eyes, heart, and central nervous system. Pulmonary parenchymal involvement is rare. To our knowledge, this is the first reported case of pulmonary cavity caused by Tropheryma whipplei. Nineteen cases of pulmonary parenchymal involvement were found by literature search. The most common respiratory symptom was cough, followed by dyspnea/breathlessness and chest pain. The most common finding in chest imaging was pulmonary nodules, followed by interstitial changes and patchy infiltration. Our case and literature review highlighted that Tropheryma whipplei infection should be considered in the differential diagnosis of pulmonary cavity, pulmonary nodules, interstitial changes, and patchy infiltration. mNGS is helpful to improve diagnosis rate.